Breathe Easier Online: Evaluation of a Randomized Controlled Pilot Trial of an Internet-Based Intervention to Improve Well-being in Children and Adolescents With a Chronic Respiratory Condition - Newcombe, Peter A; Dunn, Tamara L; Casey, Leanne M; Sheffield, Jeanie K; Petsky, Helen; Anderson-James, Sophie; Chang, Anne B (JMIR Publications, 2012)
BackgroundChronic respiratory illnesses are the most common group of childhood chronic health conditions and are overrepresented in socially isolated groups. ObjectiveTo conduct a randomized controlled pilot trial to evaluate the efficacy of Breathe Easier Online (BEO), an Internet-based problem-solving program with minimal facilitator involvement to improve psychosocial well-being in children and adolescents with a chronic respiratory condition. MethodsWe randomly assigned 42 socially isolated children and adolescents (18 males), aged between 10 and 17 years to either a BEO (final n = 19) or a wait-list control (final n = 20) condition. In total, 3 participants (2 from BEO and 1 from control) did not complete the intervention. Psychosocial well-being was operationalized through self-reported scores on depression symptoms and social problem solving. Secondary outcome measures included self-reported attitudes toward their illness and spirometry results. Paper-and-pencil questionnaires were completed at the hospital when participants attended a briefing session at baseline (time 1) and in their homes after the intervention for the BEO group or a matched 9-week time period for the wait-list group (time 2). ResultsThe two groups were comparable at baseline across all demographic measures (all F < 1). For the primary outcome measures, there were no significant group differences on depression (P = .17) or social problem solving (P = .61). However, following the online intervention, those in the BEO group reported significantly lower depression (P = .04), less impulsive/careless problem solving (P = .01), and an improvement in positive attitude toward their illness (P = .04) compared with baseline. The wait-list group did not show these differences. Children in the BEO group and their parents rated the online modules very favorably. ConclusionsAlthough there were no significant group differences on primary outcome measures, our pilot data provide tentative support for the feasibility (acceptability and user satisfaction) and initial efficacy of an Internet-based intervention for improving well-being in children and adolescents with a chronic respiratory condition. Trial registrationAustralian New Zealand Clinical Trials Registry number: ACTRN12610000214033; http://www.anzctr.org.au/trial_view.aspx?ID=308074 (Archived by WebCite at http://www.webcitation.org/63BL55mXH)